Building a Vectorial function from a fixed point given previously - Rubio López, Franco (2017)
In this paper we construct a vector function with a fixed point given previously, from the fixed points of a quadratic function. Our goal is to provide a criterion for the assignment of values to the elements of the matrix associated to the vector function, which will allow to establish the stability of the system, ensuring that said fixed point is an attractor.